Enlarged Prostate (Homoeopathy for All, 2024)
The prostate is a gland that produces  some of the fluid that carries sperm  during ejaculation. The prostate  gland surrounds the urethra, the tube  through which urine passes out of  the body. An enlarged prostate means the  gland has grown bigger. Prostate  enlargement happens to almost all  men as they get older. An enlarged prostate is often  called benign prostatic hyperplasia  (BPH). It is not cancer, and it does  not raise your risk for prostate cancer.
Keywords: small amount; testicles; symptoms